Knowledge, attitude and practice towards bio-medical waste management among healthcare workers: a northern Saudi study - Thirunavukkarasu,Ashokkumar; Al-Hazmi,Ahmad Homoud; Dar,Umar Farooq; Alruwaili,Ahmed Mohammed; Alsharari,Saleh Dhifallah; Alazmi,Fahad Adel; Alruwaili,Saif Farhan; Alarjan,Abdullah Mohammed (PeerJ, 2022)
Background Health care workers (HCWs) involved in day-to-day care and other healthcare activities play a significant role in biomedical waste (BMW) management. The World Health Organization stated some of the causes for the failure of BMW management, namely, lack of awareness of the health hazards related to BMW and inadequate trained HCWs in BMW management. The present study assessed knowledge, attitude, and practice (KAP) towards BMW management among the HCWs in northern Saudi Arabia. Methodology The present study assessed KAP through a self-administered and validated questionnaire. Using a multistage probability sampling method, 384 HCWs from different healthcare facilities participated in this survey. We performed binomial logistic regression analysis to find association between KAP subscales and sociodemographic characteristics. Spearman’s correlation test was performed to find the strength and direction of correlation (rho) between KAP scores. Results Of the population studied, high knowledge, attitude, and practice scores were found in 47.1%, 65.1%, and 49.5% of the HCWs, respectively. The present study found that knowledge score was significantly higher among the age group from 30 to 39 years (ref: age less than 30 years: AOR = 2.25, 95% CI [1.05–4.85], p = 0.04) and non- Saudi nationals (ref: Saudi: AOR = 2.84, 95% CI [1.63–4.94], p < 0.001) The attitude score towards BMW management was significantly lower among the HCWs working in tertiary care settings (ref: PHC: AOR = 0.38, 95% CI [0.12–0.69], p = 0.01). Regarding the practice score, the male categories had a significantly higher score (ref: female: AOR = 1.82, 95% CI [1.19 –2.99], p = 0.02), while pharmacist (ref: physicians: AOR = 0.39, 95% CI [0.18–0.58], p = 0.02) and lab technicians (ref: physicians: AOR = 0.31, 95% CI [0.11–0.53], p = 0.02) had a significant lower practice score. The test results revealed a weak positive correlation of knowledge with the attitude scores (rho = 0.249, p = 0.001), and a moderately strong positive correlation was found between attitude and practice scores (rho = 0.432, p = 0.001). Conclusion This study suggests that a regular training program for the HCWs on BMW management is necessary through symposiums, role play, interactive lectures, and other feasible training methods. Furthermore, a multicentric prospective exploratory study is to be conducted in other regions of the KSA to understand the region-specific training needs of HCWs.
Keywords: Biomedical waste; Knowledge; Attitude; Practice; Correlation; Healthcare workers